2009
DOI: 10.1638/2008-0167.1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Cataract and Fatty Liver in Captive Plains Viscachas (Lagostomus maximus) in Relation to Diet

Abstract: Occurrence of cataract and fatty liver in captive plains viscachas (Lagostomus maximus) in relation to diet Abstract An increased incidence of cataract and fatty liver in plains viscachas (Lagostomus maximus) was noted for many years at the Zurich Zoo. Based on elevated serum fructosamine and glucose, diabetes mellitus was diagnosed, and these parameters normalized when the diet of the animals was changed from a low-fiber to a high-fiber diet. Here, we evaluate 177 necropsy reports from before and after the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This comparison indicates that the concentrate diets used in the present study are more digestible than the diets plains viscachas probably have adapted to over evolution. The relevance of maintaining rodents susceptible to diabetic conditions on high‐fiber diets without concentrates has been repeatedly recommended in order to prevent obesity and diabetes, and this not only with respect to viscachas [Gull et al, ; Wenker et al, ] but also for degus [Edwards, ], tuco‐tucos ( Ctenomys talarum ) [Wise et al, ], agoutis ( Dasyprocta spp.) [McWilliams, ], and sand rats [Kalman et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This comparison indicates that the concentrate diets used in the present study are more digestible than the diets plains viscachas probably have adapted to over evolution. The relevance of maintaining rodents susceptible to diabetic conditions on high‐fiber diets without concentrates has been repeatedly recommended in order to prevent obesity and diabetes, and this not only with respect to viscachas [Gull et al, ; Wenker et al, ] but also for degus [Edwards, ], tuco‐tucos ( Ctenomys talarum ) [Wise et al, ], agoutis ( Dasyprocta spp.) [McWilliams, ], and sand rats [Kalman et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…They are herbivorous [Campos et al, ], with an apparent preference for grasses [Giulietti and Jackson, ; Branch et al, ; Puig et al, ; Bontti et al, ; Pereira et al, ], and have been reported to have a low metabolic rate [Kohl, ]. Nevertheless, their diet in captivity has traditionally contained varied amounts of energy dense feeds, which may trigger diet‐induced diabetes mellitus with cataract formation, similar to degus ( Octodon degus ) [Rübel et al, ; Gull et al, ; Wenker et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Formation of fructosamine is proportional to the degree and duration of hyperglycemia within the patient. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] It has also been shown to be a useful marker for differentiating nondiabetic causes of glucosuria. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] It has also been shown to be a useful marker for differentiating nondiabetic causes of glucosuria.…”
mentioning
confidence: 99%
“…Obviously, these animals are mostly characterized by blurred vision, retinal atrophy, and opacity, plus the vacuole formation has been observed in their islets of Langerhans in both α-and β-cells [ 66 ]. Rodents such as Ctenomys talarum and Lagostomus maximus provoked DM in progeny as well as in adults with noteworthy high levels of fructosamine, glucose, fatty liver, opacity, and blurred vision [ 67 , 68 ]. It is hypothesized that diminishing exercise, excessive diet, and more glucose consumption appear to be other reasons for DM as well.…”
Section: Dm In Wild Animalsmentioning
confidence: 99%